TINJAUAN PENERAPAN METODE GREEN CONSTRUCTION DAN METODE KONSTRUKSI KONVENSIONAL (STUDI KASUS: PROYEK PEMBANGUNAN MESS KARYAWAN SITE UT BENGALON MILIK PT UNITED TRACTORS TBK) - Raden Nur Muhammad Mardiansyah; Fatmawati Oemar (FTSP Universitas Jayabaya, 2022)
The construction of service facilities owned by PT United Tractors Tbk still uses conventional methods and disposable materials are not environmentally friendly. As a public company engaged in natural resource exploitation services, PT United Tractors Tbk. are required to be able to apply ESG principles in their business and investment practices. The application of the green construction concept is one of the efforts of PT United Tractors Tbk. to meet the demands of the public and fulfill the responsibility for the vision of environmentally friendly sustainable development in Indonesia. Based on the results of a comparative analysis of costs, quality and time on the walls and floors of the Employee Mess, it can be concluded that the green construction method for walls and floors works is more efficient in cost with a total percentage of 76% and efficient in time with a total percentage of 58% compared to the work conventional construction methods.